PENGARUH KOMPENSASI, MOTIVASI, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN NON MEDIS RUMAH SAKIT RETU IBU BALIKPAPAN - Yusuf , Muhammad (MEDIA RISET EKONOMI [MR.EKO], 2026)
This research aims to determine the influence of Compensation, Motivation, and Work Environment on the Performance of non-medical employees at Restu Ibu Balikpapan Hospital. The sampling technique in this research is purposive sampling with a total employee population of 352 employees at Restu Ibu Balikpapan Hospital. The data collection method is carried out using distributing questionnaires. The research uses SmartPLS to manage the results data and this research shows that the Compensation variable influences the permormance of non-medical employees at restu ibu Balikpapan hospital. Motivation variables influence the performance of non-medical employees at Restu Ibu Balikpapan Hospital. Work environment variables influence the performance of non-medical employees. The most dominant variable in the performance of non-medical employees at the Balikpapan Restu Ibu Hospital is the work environment.